Long-term financial effects of quality management system maturity based on ISO 9001 principles - Ana Kundid Novokmet; Andrijana Rogošić (Amfiteatru Economic Journal, 2017)
Accounting information was often used to determine the effect of quality management initiatives. Relation between quality management and financial performance of the companies was extensively explored but with the conflicting results. The most recent studies introduced intermediary factors between quality management and financial performance. The objective of this paper is to determine the effect of quality management system maturity of companies on their long-term financial performance. The empirical research was conducted on the large-sized companies in Croatia that hold ISO 9001 certificate. The multivariate statistical analysis was used to support the hypothesis on quality management system maturity adding to companies' financial pe rformance. Results confirmed that the companies with more mature quality management system have better long-term financial outcomes (measured by EBIT margin, ROA, solvency ratio and financial costs ratio) than the companies with the initial maturity stages of quality management system.
Keywords: G30; M41; L15; 330; quality management; accounting information; financial performance; capital structure theory; ISO 9001